Ethics, integrity and well-being in elite sport: A systematic review - Agnew, D.; Henderson, P.; Woods, C. (The Sport Journal, 2017)
Background: Athletes are expected to be good role models, compete fairly and allow the public insight into their personal lives away from sport. Objective: The purpose of this paper was to conduct a systematic review on integrity, ethics and well-being in elite level sport. Methods: A systematic search of SPORTDiscus, ScienceDirect, Taylor & Francis and Informit was conducted. The selection criteria were; published between 2006-2016, full-text availability, peer reviewed and English language. Twenty-three articles met the criteria for inclusion in this review and were analysed through an inductive thematic synthesis approach. Results: Three themes emerged through the inductive thematic synthesis approach; sportspersonship and ethics, scandal and well-being. The concept of sportspersonship extends beyond the rules of sport and is strongly linked to the character of athletes. Sports environments are a key factor in the well-being of athletes and contribute to the expectations placed on athletes, particularly with regard to winning. Conclusions: Ethics, integrity, sportspersonship and well-being are interrelated concepts in elite sport. Expectations placed on athletes may be unrealistic and may have negative consequences on well-being. It is important to understand the factors contributing to athlete well-being in order to develop strategies to minimize the adversities faced by athletes.